Pola Komunikasi Keluarga Beda Agama Dalam Membangun Keharmonisan (Studi Kasus Keluarga Beda Agama di Getasan, Semarang ) - Haninda Rafi Windiastuti; Sri Budi Lestari (Interaksi Online, 2018)
Interfaith family is a family formed from marriage of different religions where family members in it embraced a different religion. Interfaith family also has different communication with the another family. Communication pattern will influence in a relationship. Aim of this reser to describe how communication pattern in interfaith family applied to constructing harmony. Used the qualitative approach, the post-positivisme, and data analysis referring to the case study matching pattern.The subject of the research is three interfaith family in Getasan, Semarang. This research used Family Scheme Theory from Fitzpatrick and Relational Dialectica Theory from Leslie Baxter and Barbara Montgomery. The results showed that the pattern in line with the predicted earlier pluralistic pattern and consensual pattern found in this study. The consensual pattern is found in pairs 1 and 3 each of which is characterized by high conversation orientation and low compliance orientation. High conversation orientation is manifested through the involvement of all family members in communication activities with each other demonstrated through honest and open communication. While a low compliance orientation is characterized by giving decision-making authority to each family member, for example authorizing the child to choose a religion. The plural pattern found in pair 2 is characterized by high conversation orientation and high compliance orientation. Although all members engage in honest, open communication activities, decision-making authority is in the hands of parents. Despite having different communication patterns, the three pairs of different religious families can live a harmonious life that is marked by the fulfillment of harmony elements according to Dadang Hawari include running a good religious life, having time with family, having good communication, being able to respect fellow family members, the quantity of conflict is minimal and has a close bond between family members